Assessment of ovarian activity in captive goral (Naemorhedus griseus) using noninvasive fecal steroid monitoring - Khonmee J. (Elsevier Inc., 2014)
To date, there is no information on gonadal steroidogenic activity of female goral (. Naemorhedus griseus), a threatened species of Thailand. Captive goral populations have been established to produce animals for ex situ conservation and reintroduction, but as yet none are self-sustaining. The objectives of the present study were to (1) determine the influence of season on ovarian steriodogenic function; and (2) examine the relationship between gonadal hormone excretion and sexual behaviors throughout the year. Fecal samples were collected 5 to 7days/wk for 15months from 8 adult females housed at Omkoi Wildlife Breeding Center in Thailand and analyzed for ovarian steroid metabolites using validated enzyme immunoassays. Observations of sexual behaviors and mating were conducted each morning for 30min/session. Based on fecal estrogen and progestagen metabolite concentrations, the overall estrous cycle length was about 21days, with a 2- to 3-day follicular phase and an 18- to 20-day luteal phase. Sexual behaviors, most notably tail-up, increased for 2 to 3days during the time estrogens were elevated during mating. Fecal progestagens were elevated during luteal phases and increased further during gestation, which lasted approximately 7months. The lactation period was 5months, and females were anestrus for 2 to 5 of those months, with the exception of one that cycled continuously throughout. Two females conceived around 2months postpartum and so were pregnant during lactation. Birth records over the past 21years indicated young are born throughout the year. This combined with the hormonal data suggests that female gorals are not strongly seasonal, at least in captivity, although there was considerable variation among females in estrogen and progestagen patterns. In conclusion, fecal steroid metabolite monitoring is an effective means of assessing ovarian function in this species and will be a useful tool for breeding management and planned development of assisted reproductive techniques such as artificial insemination and embryo transfer.